Influence of opioid peptides on human neutrophil apoptosis and activation in vitro - Zofia Sulowska; Ewa Majewska; Katarzyna Krawczyk; Magdalena Klink; Henryk Tchórzewski (Hindawi Limited, 2002)
Background: It has been shown that cells of the immune system release opioid peptides and possess receptors for them. The concentrations of opioid peptides in the peripheral circulation rapidly increase during inflammation and acute stress response.